Incomplete lineage sorting rather than hybridization explains the inconsistent phylogeny of the wisent. (December 2018) - Wang, Kun; Lenstra, Johannes; Liu, Liang; Hu, Quanjun; Ma, Tao; Qiu, Qiang; Liu, Jianquan
Abstract The wisent or European bison is the largest European herbivore and is completely cross-fertile with its American relative. However, mtDNA genome of wisent is similar to that of cattle, which suggests that wisent emerged as a hybrid of bison and an extinct cattle-like species. Here, we analyzed nuclear whole-genome sequences of the bovine species, and found only a minor and recent gene flow between wisent and cattle. Furthermore, we identified an appreciable heterogeneity of the nuclear gene tree topologies of the bovine species. The relative frequencies of various topologies, including the mtDNA topology, were consistent with frequencies of incomplete lineage sorting (ILS) as estimated by tree coalescence analysis. This indicates that ILS has occurred and may well account for the anomalous wisent mtDNA phylogeny as the outcome of a rare event. We propose that ILS is a possible explanation of phylogenomic anomalies among closely related species. Kun Wang et al. present a genomic analysis identifying incomplete lineage sorting and hybridization in the mitochondrial DNA of the European bison (wisent). They find that incomplete lineage sorting is the most feasible explanation for the phylogenetic heterogeneity observed in Bovidae.